2005
DOI: 10.4269/ajtmh.2005.72.252
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasmodium Falciparum Isolates Encoding the P. Falciparum Chloroquine Resistance Transporter Gene K76t Polymorphism With Anemia and Splenomegaly, but Not With Multiple Infections

Abstract: Abstract. The aim of the study was to assess whether infections with Plasmodium falciparum isolates encoding the P. falciparum chloroquine resistance transporter (pfcrt) gene K76T polymorphism, a molecular marker for chloroquine resistance, are associated with multiple infections, age, or clinical signs of malaria in a semi-immune population in a holoendemic area of Burkina Faso. The parameters of interest were investigated in 210 P. falciparum-positive inhabitants. Logistic regression analysis showed that pfc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(36 reference statements)
1
3
0
Order By: Relevance
“…The overall prevalence of pfcrt mutation obtained in this study (45.4%) is similar to that reported for uncomplicated cases in neighbouring countries: 41% in Mali [13] and 43.3% in Burkina Faso [14]. However, it is markedly lower than the 88% prevalence reported by Evans et al [5] in children hospitalised in northern Ghana.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The overall prevalence of pfcrt mutation obtained in this study (45.4%) is similar to that reported for uncomplicated cases in neighbouring countries: 41% in Mali [13] and 43.3% in Burkina Faso [14]. However, it is markedly lower than the 88% prevalence reported by Evans et al [5] in children hospitalised in northern Ghana.…”
Section: Discussionsupporting
confidence: 88%
“…However, it is markedly lower than the 88% prevalence reported by Evans et al [5] in children hospitalised in northern Ghana. A recent study of in vivo chloroquine resistance study in 1e5-year-old children in Niamey reported 16.6% clinical failure [15], giving a genotype-resistance index (prevalence of the resistant genotypes divided by the prevalence of parasite resistance) of between 2 and 3, as in neighbouring countries with similar epidemiological malaria profiles: Mali [9] and Burkina Faso [14]. Whatever mild and severe the malaria cases may be, the prevalence of pfcrt mutation seems to be homogeneous in this meso-endemic zone of malaria.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Bourasso had 2,263 inhabitants of different ethnic groups in March 2011 who mainly live from subsistence farming and cattle keeping. A first cross-sectional survey, which was already described elsewhere [13,18,19], was carried out in October 2000 and served as a baseline for this study. Starting in 2009 until 2012 the survey was repeated both in October and April at the end of the rainy and dry season respectively.…”
Section: Methodsmentioning
confidence: 99%